Associação de biomarcadores do inflamassoma às diferentes formas imunopatológicas da hanseníase - Ana Luisa Gomes Mendes (2017)
Leprosy still remains a serious public health problem in Brazil. This neglected disease has a wide range of clinical and histopathological manifestations which are related to the host inflammatory and immune responses. More recently, inflammasome, a complex set of proteins, has assumed a relevant role in the inflammatory response against microbiological agents. However, the involvement of inflammasome in leprosy is poorly understood. Thus, we performed an observational, cross-sectional and comparative study of the immunophenotypic expression of inflammasome-associated proteins in different immunopathological forms of leprosy by immunohistochemistry. The intensity and percentage of NLRP3, caspase-1 and 4/5 and interleukin (IL) 1, 6 and 18 immunoreactivity in the epidermal, inflammatory infiltrate and endothelial compartments of skin biopsies were evaluated. Strong expressions of NLRP3 and inflammatory caspases 4/5 were observed in all compartments of the virchowian pole and IL6 in the endothelium of the tuberculoid pole, in addition to the low expression of caspase-1, IL1 and IL18 in these polar forms. The interpolar or borderline form showed immunophenotype predominantly similar to the Virchowian pole. Despite of the strong activation of NLRP3 inflammasome classic and noncanonical pathways in the multibacillary forms, these results demonstrate the inactivation of NLRP3 inflammasome in the leprosy, suggesting immune evasion of M. leprae, which can be used in the diagnosis or treatment of Leprosy.